Influence of copper nanoparticles on the growth characteristics of tumors in white outbreed rats - P. S. Kachesova; I. A. Goroshinskaya; G. V. Zhukova; E. V. Shalashnaya; I. A. Kaplieva; V. B. Borodulin (Исследования и практика в медицине, 2022)
Purpose of the study. To study the effect of copper nanoparticles on the characteristics of the transplanted tumors of rats, as well as to assess the dependence of the effect on the method of administration of nanoparticles.Materials and methods. In experiments on 163 white outbred male rats, 160–200 g, the size and growth rate of transplanted sarcoma 45 and Pliss' lymphosarcoma were determined in dynamics when a suspension of copper nanoparticles in physiological saline was injected intratumorally or intraperitoneally in a total dose of 10 mg/kg. Nanoparticles had a "core-shell" structure with variable diameter in the range of 30–75 nm. Contrary to other researches, we started the exposure to metal nanoparticles only when the tumors had become visible and had grown up to the sizes at which their spontaneous regression was unlikely.Results. In most animals (up to 89 %), significant antitumor effects of copper nanoparticles were obtained up to complete regression of tumors with large volumes. The effects of nanodispersed copper differed in tumors with different histological structures and growth patterns. Experiments on a transplantable, slowly growing sarcoma 45 showed a decrease in the specific tumor growth rate after a single injection of nanoparticles (1.25 mg/kg), a decrease in tumor size could be observed after 4 injections (a total dose of 5 mg/kg). In the case of a rapidly growing tumor model (Pliss' lymphosarcoma), a decrease in tumor growth rates caused by copper nanoparticles occurred at later stages of exposure, after the animals received nanoparticles at a total dose of 5–10 mg/kg. The efficiency depended on the approach of nanoparticles injection.Conclusion. In case of sarcoma 45, intraperitoneal injection of copper nanoparticles was more effective than intratumoral one, while in rats with Pliss' lymphosarcoma intratumoral injection of the nanoparticles had some advantages. The results indicate that nanodispersed copper is a promising antitumor factor. The mechanisms of regression of large transplanted tumors under the influence of copper nanoparticles are discussed.